Mopra line survey mapping of NGC 6334 I and I(N) at 3mm - Walsh, Andrew; Thorwirth, S.; Beuther, H.; Burton, M. (Oxford University Press, 2010)
A 5 × 5 arcmin2 region encompassing NGC 6334 I and I(N) has been mapped at a wavelengthof 3mm (from 83.5 to 115.5 GHz) with the Mopra telescope at an angular resolution between33 and 36 arcsec. This investigation has made use of the recently installed 3mm MonolithicMicrowave Integrated Circuit (MMIC) receiver and the Mopra Spectrometer with broad-bandcapabilities permitting total coverage of the entire frequency range with just five differentobservations. In total, the spatial distributions of 19 different molecules, ions and radicals,along with additional selected isotopologues, have been studied. Whilst most species trace thesites of star formation, CH3CN appears to be most closely associated with NGC 6334 I andI(N). Both CN and C2H appear to be widespread, tracing gas that is not associated with activestar formation. Both N2H+ and HC3N closely resemble dust continuum emission, showingthat they are reliable tracers of dense material as well as the youngest stages of high-massstar formation. Hot (Eu/k > 100 K) thermal CH3OH emission is preferentially found towardsNGC 6334 I, contrasting with I(N), where only cold (Eu/k < 22 K) thermal CH3OH emissionis found.